Political Economy and Regional Policy: The Impact of US-China Trade Tension on the Global Economic Growth - Sunkung Danso (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This paper uses a systematic literature review to discuss US-China trade tension. The study discusses the US-China trade tension and its impact on the global economy because the US-China trade war is imminent at the point in time since President Trump came to power in 2016. This research aims to examine how US-China trade tension is unfolding and the significant change of this trade tension on the world economy. The systematic literature review was engaged to capture the sequence of the event as they are happening between the US and China with regards to trade barriers. This research reviewed 19 peer-review journals and some news items and WTO resources relevant to this study. This study revealed that the US-China trade tension has affected consumer goods to some extent but it may not affect the global economy currently. However, it is evident that in the long-run; the US-China trade war will have an impact on the lives of people and the global economy if the issue continues to intensify. In conclusion, the economy of the US has declined drastically by 0.8% while China also experience 0.4% fall in the economy in 2019. The impact is currently not severe on the global economy but if the tension continues it might have a negative impact on the global economy. The trade deficit is getting wider between China and the US.